Aerodynamic design and performance parameters of a lift-type vertical axis wind turbine: A comprehensive review. (April 2021) - Hand, Brian; Kelly, Ger; Cashman, Andrew
Abstract: The high emission of fossil fuels are major driving forces in renewable energy technology development. In response, the lift-type vertical axis wind turbines (VAWT) is experiencing a renewed interest for large-scale offshore wind energy generation and also for small-scale urban devices. Significant research has been published on the aerodynamic design and optimisation of VAWTs. In this paper, an attempt is made to review the aerodynamic design parameters which influence the VAWT's aerodynamic efficiency. Each parameter is discussed in detail regarding their advantages and disadvantages. A baseline VAWT design has been put forward from this literature review to support VAWT aerodynamic analysis. Furthermore, areas of future research requiring attention have been identified to further progress the aerodynamic design and development of VAWTs. Highlights: The aerodynamic design parameters which influence the lift-type VAWT are discussed. Recommendations are made from the review and a baseline VAWT design is outlined. Design areas requiring research have been identified to progress VAWT technology.